Optimizing Semi-solid Fermentation Substrates for Enhanced Conidia Production of Nomuraea rileyi (Farlow) Samson as a Biopesticides for Insect Control - Trinh Thi, Xuan; Thi Xuan, Mai Lam; Thi Ngoc, Xuan Le; Kim, Son Pham; Thanh Quynh, Dao Truong (Research in Ecology, 2025)
Biological insecticides have gained importance in modern society because they cause minimal environmental harm and reduce pests' ability to develop resistance. Nomuraea rileyi, a facultative entomopathogenic fungus, is suitable for infecting lepidopteran pests, including Spodoptera litura and Helicoverpa armigera. This work aims to identify a suitable semi-solid fermentation medium to increase the conidia production of N. rileyi and enhance its biological control ability as mycoinsecticide. Research is carried out on broken rice, wheat, sorghum, and corn as substrates, both with and without nutrient addition. It also covers incubation under set conditions, colony harvesting, and conidial yield and germination determination using a haemocytometer. All the study was conducted using a completely randomized design (CRD) and a test of significance was set at p <0.05 using analysis of variance (ANOVA). This work aimed to establish the effect of various substrates on growth and conidia formation in N. rileyi. The highest conidia count of 10 × 10⁸ CFU/g on day 15. The result was obtained from BR + Nu followed by sorghum 7 × 10⁸ CFU/g, corn 7 × 10⁸ CFU/g and wheat 6.5 × 10⁸ CFU/g. Thus, post-drying, the highest corresponding viability was observed in the product containing BR+Nu – 6.20 ×10⁸ CFU/g. Adding rice bran (BR+RB, 150g each) still increases conidial yield up to 14×108 CFU /g at 15 DAI. These findings thus assert that broken rice and supplementation affect conidia yield and viability.